METAPHOR IN LITERARY AND LINGUISTIC CONTEXTS - Turdikulova Raykhon Turdikul qizi; Khakimov Khamidulla Inamovich (Western European Studies, 2025)
The article also provides information on the use of metaphors in literary texts, their significance, and characteristics. It also defines research conducted on the phenomenon of metaphor Uzbek and English languages and provides an analysis of the related viewpoints. Metaphor described from the perspective of new directions in linguistics as a linguistic phenomenon that reflects national worldview. It also provides several examples of metaphors in different writers’ works with classifications
Keywords: Metaphor; linguistics; literary texts